(untitled) (NAU Journal of Library and Information Science, 2021)
The study investigated the use of information by small and medium scale businesses in Zaria and Kaduna metropolis. A research question and one hypothesis were used for the study. The research method adopted was the survey method and population consisted of entrepreneurs in Zaria and Kaduna, basically small-scale entrepreneurs. The sampling of the entrepreneurs (small scale) was done using random sampling technique to select four hundred and fifty (450) entrepreneurs for Zaria and 450 entrepreneurs for Kaduna. Questionnaires were used for data collection. Percentages and Chi-Square were used to analyze the data. Out of four hundred and fifty SMEs sampled from Zaria and Kaduna, 376 and 370 valid respondents were analyzed. Chi-Square distribution at 0.05 significant level was used to test a hypothetical statement from the study’s question. Results showed that (38%) of small and medium scale business entrepreneurs in Zaria, use the information generated in their businesses for carrying out duties whereas in Kaduna, the majority which was 35% of the business entrepreneurs use the information generated for planning. On the contrary, minority of about 13% of the respondents in both Zaria and Kaduna respectively, used the information generated for all purposes in their businesses. The hypothesis’ test indicated that there were significant differences between the various entrepreneurs in Zaria and Kaduna respectively in theways they use business information for optimum performance. The study recommended that collaborative efforts be encouraged between Librarians especially those in public libraries, Industrial Development Centres (IDC) and other conventional and contemporary information centres to adequately educate the entrepreneurs on how to make efficient and effective use of the information they generate. Keyword: Information, Information Use, Small and Medium Scale Businesses, Business Information. Introduction Information is an indispensable basis of decision-making in every facet of entrepreneurship. It is a vital ingredient for the social development of nations, especially in developing countries (Thanuskodi and Kalyani, 2010). The management of information includes the organization of wide-spread facts, policy planning, development, maintenance and use of integrated systems and services. It involves the optimization of information flow and harnesses the technological requirements of its end-users, in diverse organizational status. However, the aim of information management is to promote organizational effectiveness by enhancing the capabilities of the organizations to cope with the demands of their internal and external environments in both dynamic and stable conditions. It also includes the use, maintenance and protection of such records. Leigh (2020) posits that, every business needs information to help it succeed. A combination of internal and external business information resources and its use can provide the background necessary to evaluate current performance and plan future progress of businesses. Reliable and valid information is essential to all businesses and organisations. Without reliable information and its effective and efficient use, a business will have no idea of where it stands in its market, its financial and sales figures or how to proceed in the future. Information is required so that businesses will know: - how their markets are developing, how labour markets are changing, what the economy is doing and what new laws are being passed that might affect the way of its operation. All of this information helps businesses especially small-scale businesses to make accurate decisions based on full knowledge. Incorrect decisions are likely to be the result of inadequate information use (Weebly, 2020). Indigenous businesses entrepreneurs in most developing countries like Nigeria need help in the area of information management which includes use, and that was why information centers such as Industrial Development Centers (IDC) were established. Nevertheless, there is high mortality rate of some small and medium scale businesses. The small and medium enterprise is an important drive in every stage of its growth and economic development (Egwuonwu, Mohammed and Momoh 2011). The essentiality of explicit understanding of how information is utilized in small and medium scale businesses in Nigeria has drawn the attention of conscientious indigenous information scientists. Hence, in this paper, we have focused on information use by small and medium scale entrepreneurs in Zaria and Kaduna metropolises of northern Nigeria. Information Use by Small and Medium Scale Entrepreneurs Small and medium scale businesses are non-subsidiary, independent businesses which employs fewer numbers of employees. This number varies across countries. Small and Medium Scale Enterprises (SMEs) form the bulk of the businesses in Nigeria. The attractions to the owners include being less capital intensive and flexibility in filling the need in niche markets. Their contribution to the growth of the Nigerian economy cannot be underestimated as they drive the economic and industrial transformation of the country. ( Mekwunye , 2018). According to Ayozie, Oboreh, Umukoro & Ayozie (2013) small scale businesses, small scale industries and small scale entrepreneurship are used interchangeably to man as small scale industrial firm. The featured of small-scale businesses vary from one country to the other. There are many enterprises in Nigeria categorized as small business. Most of them are in the commercial sector. In the United States, the small business administration defines a small business as one that is independently owned and operated, and meets employment or sales standard developed by the agency. Thus, in general, the specific characteristics/criteria used in describing small scale business are; 1. The number of people/persons employed. It is usually a small business, because small number of people is employed. 2. Annual Business Turnover: - The initial capital is low, so the annual turnover will also be low. 3. Local operations: - For most small firms, the area of operation is local. The employees live in the community in which the business is located. 4. The sales volume is minimal. 5. Financial strength is relatively minimal. 6. Managers are independent, and they are responsible only to themselves, or to the owners. 7. The managers are also the owners. 8. The owners of the business actually participate in all aspects of the management (i.e. the management of the enterprise is personalized) A small and medium scale enterprise is also a small business marked by a limited number of employees and a limited flow of finances and materials ( Sarokin, 2019). Essay, (2018) revealed that the Third National Development plan of Nigeria defined a small scale business as a business that employs less than ten people, or whose machinery and cost of equipment does not exceed N600,000. According to Lawinsider (2013) business Information includes all books, records, files, research and development log books, ledgers, documentation, sales literature in the possession or under control of the sellers and to the extent that such information relates to the business, including policies and procedures, owned equipment manuals and materials and procurement documentation. Sirianni,(2020) stated that the importance of business information use is that it allows a business to make informed decisions by presenting data in a way that can be interpreted by management. In this context, customer information would be useful in providing metrics surrounding client/customer engagement to determine better ways to engage or work. However, it must be stated that the value of information lies not only in the information itself, but the actions that arise from the information especially in its usage. One of the key uses of information in business is to find out more about the customers, this will enable the owner to serve their requirements. Regardless of the business size, the customer is at the core of everything done. The customer needed to be understood in order to be interacted with. The utilization of business information has direct link to information need, in that virtually all information needed are meant to be utilized for definite purposes. Therefore, it is imperative to consider what happens with the needed information once it has been obtained, and how it is applied to accomplishing a specific task or goal within a business. Statement of the Problem The turbulent and changing information environment calls for continual research to ensure that the needs of information users are satisfactorily met. Relevant expertise of professionals is often required by entrepreneurs such that they can cope with the operational management and challenges of their businesses hence plan for the future. However, there is an urgent need to understand and grasp the complex process of identifying information needs in small scale businesses, which is a very vital link between information gathering and its use. Small and medium scale entrepreneurs (SMEs) invariably function as important economic drivers in the growth and development of economies when the challenge of use of the information is put to constant check. Egwuonwu, (2012) observed that in Kaduna and Zaria many small and medium scale businesses rise and crumble. This perhaps might be connected to the fact that small businesses in Zaria and Kaduna do not adequately make use of the information generated for proper planning, controlling, and carrying out duties. Yet, it is challenging to know that entrepreneurs are often faced with the difficulty of knowing the most functional way of information usage. Purpose of the Study The purpose of this study is: To determine what the business entrepreneurs in Zaria and Kaduna use business information for. Research Question The research question formulated to guide the study is: 1. What do the business entrepreneurs in Zaria and Kaduna use business information for? Hypothesis The following hypothesis was tested at 0.05 level of significance H01: There is no significant difference between the entrepreneurs in Zaria and Kaduna in the use of business information. Methodology The study adopted a descriptive survey research design which sought information from the respondents. The design is ideal for the study because the study involved collecting data from a sample of small and medium scale entrepreneurs in Zaria and Kaduna. The population of this study consist of 900 entrepreneurs in Zaria and 900 entrepreneurs in Kaduna with basically small scale entrepreneurs such as; business centres, fast food dealers, book and stationeries dealers, dealers on computer and accessories, pharmaceuticals shops, leather goods and services, building material dealers, motor parts dealers, technicians, printers, poultry farmers, bakeries, salons, provision retailers, boutiques, electronic dealers, tailors and photographers. The sampling of the entrepreneurs (small scale) was done using random sampling technique to select four hundred and fifty (450) entrepreneurs in Zaria and four hundred and fifty (450) entrepreneurs in Kaduna. The sampling procedure included the selection of respondents from the target population in Kaduna and Zaria. Questionnaires were used for data collection. Four hundred and fifty questionnaires were distributed in Kaduna and Four hundred and fifty questionnaires were also distributed in Zaria and 376 valid respondents were fully returned in Kaduna and 370 valid respondents were fully returned in Zaria. Descriptive statistical tools such as tables, percentages were used to present and analyze the research question while Chi-square (?2) tests were used to test the null hypothesis at 0.05 level of significance. Results Research Question: What do the business entrepreneurs in Zaria and Kaduna use business information for? Tables 1a: Information Use by Business Entrepreneurs in Zaria Table 1a shows that majority (37.77 approximately 38%) of small and medium scale businesses use information generated in their day to day transactions for carrying out duties. Research Question: What do the business entrepreneurs in Zaria and Kaduna use business information for? Table 1b:Information Use by business entrepreneurs in Kaduna Table 1b shows that majority of the small and medium scale entrepreneurs (35%) use the information they generate for planning. H01 : There is no significant difference between the entrepreneurs in Zaria and Kaduna in their use of business information. Table 2a: The Contingency of the Entrepreneurs in Zaria and their Use of Business Information H01 : There is no significant difference between the entrepreneurs in Zaria and Kaduna in their use of business information. Table 2b: The Contingency of the Entrepreneurs in Kaduna and their Use of Business Information From the standard table of the critical values (Sambo, 2005; Sunder-Rao and Richard, 2007; Spiegel and Stephen, 2008) the critical value of Chi-Square at significant level of ? = 0.05 and degree of freedom (d. f.) = 54 is 72.153. The value for critical level as low as ? = 0.005 for the same d.f. is 12.8. Tables 2a and 2b show that the calculated Chi square values are 149.84 and 133.182 for Zaria and Kaduna respectively. These calculated chi squares are greater than the critical chi-square (72.153). Therefore, the hypothesis of no significant difference between the entrepreneurs of various businesses in their use of information is rejected. Discussion From the responses given in Table 1a, majority (38%) of small and medium scale business entrepreneurs in Zaria, used the information generated in their businesses for carrying out duties whereas in Kaduna (Table 1b) , the majority which is 35% of the business entrepreneurs use the information generated for planning. On the contrary, minority of about 13% of the respondents in both Zaria and Kaduna respectively, use the information generated for all purposes in their businesses. This implies that the place of information use in small and medium scale businesses needs more emphases by information providers in both Zaria and Kaduna. The entrepreneurs should be made to know that the business information which they have obtained has vast range of use and inexhaustible application for the success of their businesses. However, there is high tendency that small and medium scale businesses may forget completely and fail to make reference to the information they generate after some time lapse which may be useful for planning and effective running of their businesses. According to Wikipedia (2019) Successful entrepreneurs have the ability to lead a business in a positive direction by proper planning, to adapt to changing environments and understand their own strengths and weakness. Keeping and using information records are good in the sense that, they accurately answer legal and financial questions which may be raised by governmental agencies, banks, customers and employees. According to table 2a and 2b the critical value of Chi-Square at significant level of ? = 0.05 and degree of freedom (d. f.) = 54 is 72.153. The value for critical level as low as ? = 0.005 for the same d.f. is 12.8. Tables 2a and 2b show that the calculated Chi square values are 149.84 and 133.182 for Zaria and Kaduna respectively. These calculated chi squares are greater than the critical chi-square (72.153). Therefore, the hypothesis of no significant difference between the entrepreneurs of various businesses in their use of information is rejected. In other words, the chi-square values 149.84 and 133.182 with degree of freedom (54) are feasible at probabilities of about 5.9889E-08 and 1.2353E-08 respectively (Tables 2a and 2b) with which the hypothesis was proposed. This also justifies the rejection of the hypothesis. This implies that there are differences between the various entrepreneurs both in Zaria and Kaduna in theways they use the business information which they have acquired for optimum performance. For instance, the contingency Tables 2a and 2b show that most of business centres in Zaria and Kaduna use their information for carrying out duties when compared with other businesses in the two metropolises. In Zaria, majority of the poultry farmers use their business information to control their businesses than other business entrepreneurs do. In Kaduna, the results show that upholstery makers, hair dressers, and electronic dealers use their business information to control their businesses more than other business entrepreneurs do. Business centres have the highest frequency in the use of their business information for all purposes more than several other businesses in both Zaria and Kaduna. Hence, the rejection of the hypothesis does not rule out the possibility that differences in the customers’ relationships to the various entrepreneurs result to the differences in the use of acquired information in the two metropolises. For example, while the pharmaceuticals use their business information to control the quality of drugs they sell by avoiding fake drugs in order to satisfy their customers’ demands, upholstery makers use theirs for planning the models and designs of their products in order to make them impressive to their customers. Conclusion Based on the foregoing survey, data and analyses on information use, this paper has portrayed the attitude of small and medium scale businesses in Zaria and Kaduna metropolises. The frequency distribution data showed obvious differences between various calibres of the entrepreneurship sampled in both Zaria and Kaduna towns. This study has shown that most Zaria SMEs incline to the use of their business information for carrying out their immediate transactions. In Kaduna, most of the SMEs tend to use their information for planning and controlling their businesses for optimum transactions. The contingencies between the various SMEs in Zaria and Kaduna respectively and their use of business information have shown that the peculiarity in each kind of entrepreneurship determines the attitude of the utilization of business information. Hence the point to the fact that at 0.05 significant level that is, 95% confidence level in the analysis, there is a significant difference between the varieties of entrepreneurs in both cities of northern Nigeria. Thus, it is accentuated that indigenous information providers should at the point of acquainting the SMEs with business information, enlighten them on the usage capacities of what they receive. Emphases should also be laid on the usefulness of the certain information to some particular businesses. However, the present status of the SMEs with respect to information usage in the two metropolises is a function the enlightenment offered to them from time to time. Recommendations: The study on the information use by small and medium scale entrepreneurs in Zaria and Kaduna, northern Nigeria has shown that there is a need for transformation in the use of information by small and medium scale businesses in Zaria and Kaduna metropolis. i. Collaborative efforts are encouraged between Librarians especially those in public libraries, Industrial Development Centres (IDC) and other conventional and contemporary information centres to adequately educated the entrepreneurs on how to make efficient and effective use of the information they generate. ii. Schools and departments of librarianship and information studies should offer practical and goal-oriented courses on business information and management in various fields and levels of entrepreneurship. This will cause graduates to cope with the challenge of information needs in their various careers after school. References Ayozie, D., Oboreh J. , Umukoro F. &Ayozie V. (2013) . Small and Medium Scale Enterprises (SMES) in Nigeria the Marketing Interface. In Global Journal of Management and Business Research Marketing 13 (9), Retrieved from https://globaljournals.org/GJMBR 3/1-Small-and-Medium-Scale-Enterprises.pdf EgwuonwuU.,Mohammed Z., and Momoh K. (2011). Information Storage and Dissemination by Small and Medium Scale Entrepreneurs in Zaria and Kaduna. Pacific Journal of Science and Technology.12(1),277-285. Retrieved from: http://www.akamaiunuversity.us/PJST.htm Egwuonwu U.I. (2012). The Impact of Education on the Use of ICT by Small and Medium Scale Entrepreneurs in Zaria and Kaduna. Pacific Journal of Science and Technology 13(1) p.419. Retrieved from: http://www.akamaiunuversity.us/PJST.htm Essays, U. K. (2018). Importance of Small and medium Enterprises in Nigeria. Retrieved from https://www.ukessays.com/essays/economics/importance-of-small-and- medium-enterprises-in-nigeria-economics-essay.php Lawinsider (2013). Business information Retrieved from https://www.lawinsider.com/dictionary/business-information Leigh, R (2020). What Types of Information Resources Does a Business Usually NeedSmall Business. Chron.com, Retrieved from http://smallbusiness.chron.com/types-information-resources-business-usually-need-4753.html . Mekwunye , U. (2018). Nigeria: Small and Medium Scale Enterprises in Nigeria – An Overview of Initial Set up. Retrieved from https://www.mondaq.com/Nigeria/CorporateCommercial-Law/757432/Small And-Medium-Scale-Enterprises-In-Nigeria-An-Overview-Of-Initial-Set-Up Sambo, A. A. (2005). Research Methods in Education. Lagos: Stirling-HordenPublishers Ltd., pp.234-276, 309-354. Sarokin, D. (2019) Small business Hearst Newspapers , Retrieved from LL. https://smallbusiness.chron.com/definition-smallscale-enterprise-17652.html Sirianni, A. (2020) The Importance of Information. Abbotsford, Melbourne, Dcode Group.https://www.dcodegroup.com/blog/the-importance-of-data-and-information-in-business Spiegel, M. R. and Stephen, L. J. (2008). Statistics.Schaum’s Outliners. Mc-Graw-Hill Publishers. Int. pp. 294-299. Sunder-Rao, P.S.S. and Richard, J. (2007). Introduction to Biostatistics and Research Methods 4th Ed. Asoke K. Ghosh Publishers, pp. 16-25, 94-99. Thanuskodi, S., Kalyani, K. S. (2010). Information Support Systems for Small-Scale Industries in Salem District: With Special Reference to Tapioca Processing Industries . Library Philosophy and Practice. University of Toronto. p.1,13. Weebly (2020).What are the different purposes of information. Retrieved from: https://teachingwithcrump.weebly.com/p1-understanding-different-types-of-business-information.html Wikipedia (2019). https://en.wikipedia.org/wiki/Small_business